2016
DOI: 10.1099/jgv.0.000591
|View full text |Cite
|
Sign up to set email alerts
|

Multi-reassortant G3P[3] group A rotavirus in a horseshoe bat in Zambia

Abstract: 33Group A rotavirus is a major cause of diarrhoea in humans, especially in young 34 children. Bats also harbour group A rotaviruses, but the genetic backgrounds of bat 35 rotavirus strains are usually distinct from those of human rotavirus strains. We identified 36 a new strain of group A rotavirus in the intestinal contents of a horseshoe bat in Zambia. 37Whole genome sequencing revealed that the identified virus, named 38 RVA/Bat-wt/ZMB/LUS12-14/2012/G3P [3], possessed the genotype constellation 39

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
(1 reference statement)
0
16
0
Order By: Relevance
“…However, the genetically close relationships of the VP7, VP4, VP6, NSP3 and NSP5 gene segments of the study strain to bat strain 3081/BRA and/or bat-like human strain Ecu534, suggest that RVA/Human-wt/SUR/2014735512/2013/G20P[28] is of bat origin. A few investigators have reported the detection of human RVAs genes in bat RVA strains (Esona et al, 2010; Sasaki et al, 2016; Waruhiu et al, 2017), but this report represents only the second time bat RVAs gene segments have been found in a human RVA strain (Solberg et al, 2009). …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the genetically close relationships of the VP7, VP4, VP6, NSP3 and NSP5 gene segments of the study strain to bat strain 3081/BRA and/or bat-like human strain Ecu534, suggest that RVA/Human-wt/SUR/2014735512/2013/G20P[28] is of bat origin. A few investigators have reported the detection of human RVAs genes in bat RVA strains (Esona et al, 2010; Sasaki et al, 2016; Waruhiu et al, 2017), but this report represents only the second time bat RVAs gene segments have been found in a human RVA strain (Solberg et al, 2009). …”
Section: Resultsmentioning
confidence: 93%
“…Several improvements in viral detection and characterization methodologies such as high-throughput next generation sequencing have led to a successful discovery and characterization of several novel viruses in bats, including enteric pathogens such as RVA (Luis et al, 2013; Waruhiu et al, 2017). However, since the first detection and characterization of a human-bat reassortant RVA from a Straw-colored Fruit bat in 2010 (Esona et al, 2010), a few of other bat RVA strains, detected and characterized from different bat species and different geographic locations have been reported (Asano et al, 2016; He et al, 2013; Sasaki et al, 2016; Waruhiu et al, 2017; Xia et al, 2013; Yinda et al, 2016). Among the reported bat RVA strains, only bat RVA strain 3081/BRA from Brazil was closely related in the VP7, NSP3 and NSP5 gene segments with the study strain from Suriname.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the subsequent decade, sporadic and scattered reports have been published about RVA strains in bats collected from serum, gut, and fecal samples in insectivorous and fruit bats. Several of these reports came from Chinese studies (24-27), but bat RVAs were also detected and (partially) characterized from France (28), Brazil (29), Zambia (30,31), Cameroon (32), Kenya (33), and Saudi Arabia (34). These studies investigated samples from a variety of bat families, such as Rhinolophidae (24, 30), Hipposideridae (25,26), Vespertilionidae (26,28), Molossidae, Phyllostomidae (29), Emballonuridae (26,33), Pteropodidae (23,(31)(32)(33)(34), and Rhinopomatidae (34).…”
mentioning
confidence: 99%
“…During the subsequent decade, sporadic and scattered reports have been published about RVA strains in bats collected from serum, gut and faecal samples in insectivorous and fruit bats. Several reports of bat RVA strains came from Chinese studies (26)(27)(28)(29), but bat RVAs were also detected and (partially) characterized from France (30), Brazil (31), Zambia (32,33), Cameroon (34), Kenya (35) and Saudi-Arabia (36). These studies investigate (36) and Eidolon helvum (25,33,34,36).…”
Section: Introductionmentioning
confidence: 99%